Pengetahuan dan Sikap terhadap Perilaku Pencegahan COVID-19 - Nopia Wati; Heni Helvia; Agus Ramon; Riska Yanuarti; Oktarianita Oktarianita (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the relationship between knowledge and attitudes towards Covid-19 prevention behavior at the Pancasila Islamic Boarding School in Bengkulu City. This research method is a quantitative research with cross sectional method. The results of the univariate analysis showed that 55.9% of students had good knowledge, 50.00% of students had an attitude of supporting Covid-19 prevention, and 55.9% of students behaved well in preventing Covid-19. The results of the chi-square test obtained that the p-value between knowledge and attitudes with Covid-19 related to Covid-19 prevention was 0.539 and 1,000. In conclusion, there is no relationship between knowledge and attitudes with Covid-19 prevention behavior at the Bengkulu City Pancasila Islamic Boarding School. Keywords: COVID-19 Prevention, Knowledge, Attitude